Vocational education and training in Italy : short description - (:unkn) unknown (Publications Office of the European Union, 2014)
This overview of the vocational education and training system in Italy is published during the Italian Presidency of the Council of the EU (1 July - 31 December 2014). It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. The 2014 Italian EU Presidency takes place in times of economic downturn and high youth unemployment. Against this backdrop, "Italy has set itself a strategic objective to strengthen VET and to expand apprenticeship-type schemes. A recent policy package, with a focus on the youth guarantee scheme and measures to reduce red tape for enterprises and promote inter-firm cooperation, reflects the need to link education and training better with the labour market, extend work-based learning schemes, ensure teachers' and trainers' professional development, and strengthen vocational guidance. This report provides an insight into Italian VET and recent developments." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; G 1.2 Arbeitsmarkt; L 5 Beratung & Orientierung; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Arbeitsmarkt; Früherkennung; Berufsberatung; Italien